Evaluasi Performa Termal dan Listrik Robinson Engine dengan Fluida Kerja Uap Bertekanan Rendah dari Boiler Kecil - Murahmad Parulian Marbun; Jufrizal Jufrizal; Indra Hermawan (CV. IRA PUBLISHING, 2025)
This study evaluates the thermal and electrical performance of a Robinson steam engine powered by low-pressure steam (≤ 2.5 bar) from a small boiler. Experiments were conducted by varying the steam pressure from 0.5 to 2.5 bar to observe its effects on voltage, current, and power output. Results show that increasing steam pressure raised the voltage from 0 V to 4.52 V and the power output from 0 W to 6.1 W. The total electrical energy generated was 9.726 kJ, with an average conversion efficiency of 0.2127% and a peak efficiency of 0.3045% at 2.5 bar. Despite the low efficiency, the system demonstrates potential for small-scale power generation and educational use in energy conversion studies.